A PROPOSED CONCEPT OF RISK CULTURE IN INDONESIA'S SHARIAH BANKING - Saimara Sebayang; Sukiman Sukiman; Rizal Agus (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to prove the proposition that organization, leadership, and competence are important factors in forming a risk culture model to strengthen risk management in the context of Indonesia's Shariah Bank, particularly Bank Syariah Mandiri. The authors will use a quantitative deductive approach to build a theoretical model, multiple hypotheses, and data to test the hypotheses in this study. The study will apply structural equation modeling (SEM), a statistical technique that employs a confirmatory approach to analyze a phenomenon's structural theory. Keywords: Risk Culture, Sharia Risk Management, Bank, Organization, Leadership,